XÂY DỰNG PHƯƠNG TRÌNH CHUYỂN ĐỘNG CỦA SÚNG ĐẠI LIÊN KHI BẮN - Huy Chương, Phạm (Vietnam Journal of Science and Technology, 2014)
This paper presents a method to build equations describing the motion of space guns when fired using coordinate transformation matrices. The system of motion of nonlinear differential equations is presented in matrix form so it is convenient to be solved by using numerical methods. Từ khóa: súng tự động, động lực học, đại liên Keywords: guns, dynamic.